Analisis Kualitas Pelayanan dan Lokasi terhadap Kepuasan Konsumen pada Warkop Syekar Bireuen - Haryani, Haryani; Safrina, Emi; Diah, Muhammad; Firmansyah, Denny (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to determine the effect of service quality and location on consumer satisfaction at Warkop Syekar. This type of research is associative research. Data collection in this research was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 100 respondents, while the population used in this research was warkop on mada consumers. Data collection techniques were carried out using interviews, questionnaires and documentation studies. The data analysis tool used in this research uses SPSS (Statistical Product Software Solution). The data analysis techniques in this research are descriptive analysis, multiple linear regression analysis, hypothesis testing using a partial significant test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The results of this research show that partially service quality has a positive and significant influence on consumer satisfaction. And partially location has a positive and significant influence on consumer satisfaction.